Analysis of the Learning Interest Profile of Fourth-Grade Students at MI Nurul Islahil Islami in the IPAS Subject in the 2024–2025 Academic Year - Baiq Dila Sari Dewi (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
This study aims to examine the learning interest profile of fourth-grade students at MI Nurul Islahil Islami in the Integrated Science and Social Studies (IPAS) subject in the 2024–2025 academic year. The research employed a quantitative, descriptive method. The research subjects were all 29 fourth-grade students, determined using a total sampling technique. The data collection instrument was a closed-ended questionnaire with two response options ("Yes" and "No") for four indicators of learning interest, as outlined by Slameto (2010): enjoyment, student engagement, interest, and attention. Data were analysed descriptively using percentages and classification categories. The findings show that students' interest in IPAS is generally low, with 50% classified as low, 35% as medium, and 15% as high. Based on the indicators, enjoyment (55% low), interest (65% low), and attention (60% low) were in the low category, while student engagement (35% low, 40% medium, 25% high) was in the medium category. These results indicate that learning tends to be passive because the teacher predominantly uses lecture methods without support from learning media, resulting in students' engagement, enthusiasm, and focus not being optimal. The implications of this study highlight the need for more varied, interactive learning strategies supported by visual media to increase students' interest in IPAS.